Reforming the Russian Budget System : A Move to More Devolved Budget Management? - Diamond, Jack (IMF Working Papers; Working Paper, 2005)
The Russian federal government has recently initiated a fundamental reform of its budget system, encompassing important policy, procedural, and institutional changes. This paper reviews this reform agenda with reference to the experience of industrial countries that over the past two to three decades have followed a similar reform path toward a more devolved budget management system. From this perspective, the importance of the strength of existing public expenditure management systems to accommodate increased devolution and the scope for employing decentralized agencies is explored. An assessment of the present Russian reform plans in light of this review reveals a number of concerns. First, the speed of the reforms contemplated appears overly ambitious when judged by the experience of other countries. Second, the preparedness of budget institutions is questionable. Third, change management capacity needs strengthening with a more carefully defined strategy. Last, in light of these concerns, it is argued that the scope and "big-bang" approach of the current reform plans may need reformulation into a more sequenced strategy with clearer reform priorities.